FASILITAS HOTEL SEBAGAI FAKTOR PENENTU LOYALITAS PELANGGAN DI HOTEL VERTU HARMONI JAKARTA - Abigail Barus; Agista Puja N; Aura Ayunisa S; Dona Sumbara; Istar Nur A; Reyhan Athalla F (JURNAL PARIWISATA VOKASI, 2025)
The hospitality industry in Jakarta faces intense competition in the wake of tourism recovery, requiring hotels to not only provide accommodation, but also a satisfying experience through comprehensive facilities. This study aims to analyze the effect of facility completeness on customer loyalty at Hotel Vertu Harmoni Jakarta, a four-star hotel. Using a quantitative method with an associative approach, data was collected from 250 respondents selected through purposive sampling. Data analysis was performed using validity and reliability tests, descriptive analysis, and Spearman's rank correlation with the help of SPSS version 25. The results showed that facility completeness had a positive and significant relationship with customer loyalty, with a correlation coefficient of 0.436 (moderate). This finding indicates that although physical facilities such as rooms and public areas were rated very good, improvements in facility maintenance were still needed to ensure long-term loyalty.